Time series analysis of crime deterrence on drug abuse in Jalingo Local Government Area, Taraba State, Nigeria - Aideyan*†, D.O.; Adanaa†, F.C.; Kadaro†, P.M. (International Journal of Mathematical Analysis and Modelling, 2023)
Time Series on crime deterrence on drug abuse was carried out in order to determine the trend and tendency of crime and the effect of drug abuse, unemployment, and number of arrest on crime. After careful analysis, it was discovered that in the year 2017, the number of crime reported is 291 which was less than other figures used in the analysis and more forecast for subsequent years 2018, 2019 and 2020 with reported forecast rising to a high level of 414, 484 and 454 respectively. 77.3% on the variation in the crime was explained by the number of arrest, unemployment rate and drug abuse cases. The coefficients indicate that drug abuse cause increase in crime while previous arrest cause decrease in crime rate. This could be as a result of using previous information.